1990
DOI: 10.1038/bjc.1990.381
|View full text |Cite
|
Sign up to set email alerts
|

The radiation dose-rate effect in two human neuroblastoma cell lines

Abstract: Summary The current use of targeted radiotherapy in the treatment of neuroblastoma has generated a requirement for further information on the radiobiology of these cells. Here we report on studies of the dose-rate effect in two human neuroblastoma cell lines (HX138 and HX142) and the recovery that they demonstrate in split-dose experiments. The sensitivity of the two cell lines to high dose-rate irradiation was confirmed. Surviving fractions at 2 Gy were 0.083 for HX138 anc' 0.11 for HX142. There was little ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Similar observations were previously made with human neuroblastoma cells receiving g rays at a dose rate range of 10 to 900 mGy/min; however, a lower dose rate of 2.5 mGy/min was found to have a less deleterious effect. 22 For human normal dermal fibroblasts and melanoma cells following X-ray irradiation, 1120 mGy/min was much more damaging than 8.8 mGy/min. 23 Enn et al (2004) found that there was no major dose rate effect (1.8 vs 220 mGy/min) in human lung adenocarcinoma cells A549.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar observations were previously made with human neuroblastoma cells receiving g rays at a dose rate range of 10 to 900 mGy/min; however, a lower dose rate of 2.5 mGy/min was found to have a less deleterious effect. 22 For human normal dermal fibroblasts and melanoma cells following X-ray irradiation, 1120 mGy/min was much more damaging than 8.8 mGy/min. 23 Enn et al (2004) found that there was no major dose rate effect (1.8 vs 220 mGy/min) in human lung adenocarcinoma cells A549.…”
Section: Discussionmentioning
confidence: 96%
“…The lowest dose rate of 24.6 mGy/min was in a range that would be considered low in radiation oncology and cellular radiobiology experiments. [21][22][23][24] However, 24.6 mGy/min is relatively higher than both the environmental contamination/occupational exposure levels associated with radioactive fallout accidents [25][26][27][28] and the UNSCEAR's recommended low dose rate of <0.1 mGy/min (UNSCEAR 2012). 29 The other 3 dose rates used here would generally be considered high.…”
Section: Irradiationmentioning
confidence: 99%
“…The experimental values were gained with exponential recovery fits to split dose experiments [21] , [33] , [36] , [37] . The listed values resulting from a fit of the Incomplete Repair model (IR model) or the Lethal Potentially Lethal model (LPL model) to cell survival curves are taken from the following publications: [36] , [37] , [40] . The values given for the GLOBLE (which correspond to HLT i ) were determined with fits to experimentally measured cell survival data as shown in the results of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Courdi et al (1992) reported a value of 1.85 Gy for the CHP100 cell line, Holmes et al (1990) gave values of 5.00 Gy for the HX138 cell line and 9.38 Gy for the HX142 cell line, and Marchese et al (1987) reported a value of 17.59 Gy for the SK-N-SH cell line. In Fertil and Malaise (1985), Malaise et al (1987) and Amin et al (1995), NB was included among highly responsive tumours and values of 7.11 Gy, 8.31 Gy and 13.08 Gy were respectively reported.…”
Section: 2analysis Of Fractionated 131 I-mibg Treatment Of Nbmentioning
confidence: 99%